Biodiesel Production from Vegetable Oil over Plasma Reactor: Optimization of Biodiesel Yield using Response Surface Methodology - Istadi Istadi; Didi Dwi Anggoro; Putut Marwoto; Suherman Suherman; Bambang Tri Nugroho (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2009)
Biodiesel production has received considerable attention in the recent past as a renewable fuel. The production of biodiesel by conventional transesterification process employs alkali or acid catalyst and has been industrially accepted for its high conversion and reaction rates. However for alkali catalyst, there may be risk of free acid or water contamination and soap formation is likely to take place which makes the separation process difficult. Although yield is high, the acids, being corrosive, may cause damage to the equipment and the reaction rate was also observed to be low. This research focuses on empirical modeling and optimization for the biodiesel production over plasma reactor. The plasma reactor technology is more promising than the conventional catalytic processes due to the reducing reaction time and easy in product separation. © 2009 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)